STRUCTURE DIAGRAM OF GRAPHITIZED STEELS - S. V. Belikov; I. P. Volchok; V. A. Savchenko; N. A. Svidunovich; S. E. Belskij; D. V. Kuis (Литьë и металлургия)
Influence of thickness of casting wall and the carbon and silicon contents on structure formation processes in modified graphitized steels is investigated.